Genetic Diversity in Fiber Related Traits of Tossa Jute (Corchorus Olitorius L.) Germplam (SAARC Journal of Agriculture, 2021)
Genetic diversity of twenty-one genotypes of tossa jute was studied through Mahalanobis D2 statistic and principal component analysis for 15 quantitative traits related to yield at the research farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. The genotypes were grouped into four clusters. Cluster III contained the highest number of genotypes (nine), while cluster II had the lowest number of genotypes (three). The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the cluster. The highest intra-cluster distance was noticed for the cluster I and the lowest for cluster IV. The genotypes from cluster I could be selected as parents for hybridization for producing transgressive segregants. The highest inter-cluster distance was found between clusters I and IV followed by clusters I and III and the lowest was between clusters III and IV. Cluster IV recorded the highest mean value for plant height, base diameter, root length, leaf area, fresh weight with and without leaves, dry fiber weight and dry stick weight. In the total divergence, the highest contribution was recorded in plant height (65.1%) followed by base diameter (16.6%). The first two principal components, whose eigen values were greater than one, accounted for 81.7% of the total variations among the genotypes for fifteen fiber related traits. Considering the magnitude of cluster distance, cluster means for different characters and contribution of characters towards divergence, the genotypes G17, G18 from cluster IV; G1, G2, G5, G10, G16 from cluster I and G4 from cluster III could be selected as promising parents for hybridization program.SAARC J. Agri., 18(2): 27-37 (2020)